Modelagem e simulação da transferência de massa ao longo de membranas cilíndricas - Almeida, Edson Luiz Ferreira de (2011)
This dissertation sought to understand the mechanisms of mass transfer along the inner surface of cylindrical microfiltration membranes, which are associated with phenomena of diffusion and convection of one or more chemical species in a suspension. The chemical species present in the suspension are separated based on differences between the sizes of particles in relation to the average diameter of pore membrane. The driving force used in the separation process is the transmembrane pressure at which the membrane is submitted. Mathematical models capable of representing the concentration profile of solute along the membrane were used and solved using the lines method with finite differences in order to describe, in general, the behavior of chemicals, especially enzymes, along with cylindrical membranes (hollow fibers or capillary membranes or tubular membranes). Tangential filtration process was studied in the transient and permanent flow. The data obtained with the solutions of the model were compared with experimental data obtained from literature for the á and â amylases enzymes from corn malt (Zea mays) and found that the numerical method of finite differences used to solve the numerical model produced consistent results with experimental data and they are representative of the phenomenon.